Pengujian Sistem Informasi Inventaris pada Perusahaan Distributor Farmasi Menggunakan Metode Black Box Testing - Ayu Rizkita Agung; Saifudin Husen; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Management and control in the field of pharmaceutical distribution requires planning and inventory control of pharmaceutical products, because the previous system had inaccurate stock management, the performance of the previous system was slow, and it was not structured to handle large amounts of data. Therefore this research was conducted to test the inventory information system at pharmaceutical distributor companies using the black box testing method. This method was chosen because it focuses on testing system functionality without regard to the internal structure or implementation details. The results of the study show that the black box testing method is effective in testing inventory information at pharmaceutical distributor companies. This test reveals several malfunctions and input errors that may occur in system usage. By using this method, companies can identify and fix these problems before the system is fully implemented.